Long-term persistence of gene expression from adeno-associated virus serotype 5 in the mouse airways. - Sumner-Jones, S; Davies, L; Varathalingam, A; Gill, DR; Hyde, S (2006)
Recombinant adeno-associated virus vectors based on serotype 2 (rAAV2) have been used to deliver transgenes to the airways in a variety of pre-clinical and clinical studies. Gene transfer in these studies has been severely restricted by the basolateral localization of rAAV2 receptors. Here, we studied vectors constructed from the AAV5 genome and capsid, which utilize N-linked sialic acid-containing receptors found on the apical surface of airway epithelial cells. We investigated gene transfer efficacy and duration of transgene expression following delivery of rAAV5/5 vectors to the mouse respiratory tract. Robust, dose-dependent transgene expression was observed in the epithelium lining the nose for at least 32 weeks, and for at least 52 weeks in the lung. Importantly, in the lung, transgene expression mediated by rAAV5/5 was 40-fold greater than by rAAV2/2 vectors. A distinct cellular preference for rAAV5/5-mediated transduction was observed, with transgene expression being predominantly restricted to sustentacular cells of the olfactory epithelium in the nose and alveolar type II cells in the lung. Administration of rAAV5/5 vectors to both the nose and lungs led to the rapid development of rAAV5/5-neutralizing antibodies, suggesting that repeated administration may be severely hampered by host immune responses.